2020
DOI: 10.3390/w12030733
|View full text |Cite
|
Sign up to set email alerts
|

New Sustainable Approach for the Production of Fe3O4/Graphene Oxide-Activated Persulfate System for Dye Removal in Real Wastewater

Abstract: Persulfate (PS)-activated, iron-based heterogeneous catalysts have attracted significant attention as a potential advanced and sustainable water purification system. Herein, a novel Fe 3 O 4 impregnated graphene oxide (Fe 3 O 4 @GO)-activated persulfate system (Fe 3 O 4 @GO+K 2 S 2 O 8 ) was synthesized by following a sustainable protocol and was tested on real wastewater containing dye pollutants. In the presence of the PS-activated system, the degradation efficiency of Rhodamine B (RhB) was significantly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…Moreover, competition between carbonaceous substances will increase for free radical scavengers and free radicals due to the non-selective reactivity of free radicals. In many studies, the same effect in dye concentration was observed (Salari et al 2009 ; Saputra et al 2013 ; Frontistis et al 2015 ; Pervez et al 2020 ).…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…Moreover, competition between carbonaceous substances will increase for free radical scavengers and free radicals due to the non-selective reactivity of free radicals. In many studies, the same effect in dye concentration was observed (Salari et al 2009 ; Saputra et al 2013 ; Frontistis et al 2015 ; Pervez et al 2020 ).…”
Section: Resultssupporting
confidence: 55%
“…The reasons for this are; firstly, it is suitable for the production of reactive species with the increase in PS, which provides the appropriate amount of reactive for the oxidation of contaminants, and it enables easy reaction with the catalyst. Secondly, excessive use of PS decreases the formation of both economic and sulfate radicals (Pervez et al 2020 ). In other words, the sulfate radical may react with each other and turn into S 2 O 8 2− , this may lead to a decrease in efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations